2017
DOI: 10.1080/14494035.2017.1287999
|View full text |Cite
|
Sign up to set email alerts
|

Higher education governance and policy: an introduction to multi-issue, multi-level and multi-actor dynamics

Abstract: This thematic issue introduces the multifaceted nature of contemporary public policy-its multi-level, multi-actor and multiissue features-using the case of higher education policies from around the world. To do so, this introduction first describes how higher education as a policy sector should be garnering far more attention from scholars interested in political, economic and social transformation. A framework for identifying and accounting for how the 'multi-s' characteristics configure and re-configure publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 53 publications
0
20
0
3
Order By: Relevance
“…Hussler, Picard, and Tang 2010; Hewitt-Dundas 2012), without considering HEIs' stakeholder prioritisation. On the other hand, stakeholder engagement has been discussed in the context of HE governance (Bleiklie and Kogan 2007;Chou et al 2017), and with regard to the alignment of curricula to different stakeholders and particularly students (stakeholder curricula, e.g. Osborne, Davies, and Garnett 1998), but not so much in relation to HEIs' overall missions.…”
Section: Introductionmentioning
confidence: 99%
“…Hussler, Picard, and Tang 2010; Hewitt-Dundas 2012), without considering HEIs' stakeholder prioritisation. On the other hand, stakeholder engagement has been discussed in the context of HE governance (Bleiklie and Kogan 2007;Chou et al 2017), and with regard to the alignment of curricula to different stakeholders and particularly students (stakeholder curricula, e.g. Osborne, Davies, and Garnett 1998), but not so much in relation to HEIs' overall missions.…”
Section: Introductionmentioning
confidence: 99%
“…In presenting the findings of the study, we follow the three categories proposed by Chou et al (2017), examining first the distribution of authority across the stakeholder groups (the category of multi-level characteristics), then analyzing the heterogeneity of values among stakeholders (the category of multi-actor characteristics) and, subsequently, describing the complementarities and clashes between stakeholder groups (the category of multi-issue characteristics). Within each section, we describe the unique themes that emerged from the data.…”
Section: Resultsmentioning
confidence: 99%
“…federalism), and Type II, where the focus is on issue or task jurisdictions across different levels of authority where jurisdictions may overlap (as in international education). These two categories may not be sufficient to examine stakeholder dynamics across policy sectors, as each sector might have a distinct method of coordination and uphold their unique sectorial rationales (Vukasovic et. al., 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…While (higher) education was once declared a neglected policy field (Jakobi, Martens, & Wolf, ), much effort has been made by scholars to understand public policy coordination in higher education using the governance concept and its analytical potential (Braun & Merrien, ; Clark, ; Dobbins & Knill, ; Huisman, ; Schimank, ). Subsequently, comprehensive research revealed the (co‐)existence of different multilevel institutional arrangements (Benz, ; Capano, ; Chou, Jungblut, Ravinet, & Vukasovic, ; Peters & Pierre, ) departing from the overused governance‐concept by widening the scope of the original approach. By then, governance was threatened to be reduced to a “catch‐all” term (Lange and Schimank , p. 18) or to an “empty signifier” (Offe, ).…”
Section: Introductionmentioning
confidence: 99%